2003
DOI: 10.1183/09031936.03.00053202
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in lung vulnerability to tobacco smoking

Abstract: Studies have indicated that females are more vulnerable to the deleterious effect of tobacco smoking than males. The current study aimed to investigate the associations between tobacco smoking and reported respiratory symptoms, self-rated health, and lung function by sex.In 1995-1997 65,225 subjects aged o20 yrs (71% of invited) attended for screening within the Nord-Trøndelag Health Study. Among these, 10,941 subjects selected randomly or because they reported having asthma or asthma-related symptoms, partici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
83
1
5

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(99 citation statements)
references
References 32 publications
10
83
1
5
Order By: Relevance
“…This finding is in accordance with data that show females have a relatively strong airway responsiveness during Mch provocation testing compared with males [8][9][10][11]22]. It has been suggested that the greater female airway responsiveness is due to the fact that females have a smaller airway calibre than males [22].…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…This finding is in accordance with data that show females have a relatively strong airway responsiveness during Mch provocation testing compared with males [8][9][10][11]22]. It has been suggested that the greater female airway responsiveness is due to the fact that females have a smaller airway calibre than males [22].…”
Section: Discussionsupporting
confidence: 82%
“…Moreover, to further explore individual risk factors for susceptibility to air pollution males and females were investigated separately. Females are known to have a higher degree of AHR than males, which has been related to increased susceptibility to the effect of environmental exposures, such as tobacco smoke, irritants and allergens [8][9][10][11]. Therefore, females with increased IgE and AHR may constitute a group at high risk for effects of air pollution on the respiratory system.…”
mentioning
confidence: 99%
“…However, the JEM-based exposure characterization is less subject to recall bias than the self-reported exposure characterization (6,19,20). Thus, a tendency for a stronger relationship between airborne occupational exposures and asthma, and symptoms in women could be due to women being more vulnerable to airborne pollutants than men (21,22). The results also indicate that women seem to develop respiratory symptoms at a lower exposure-level compared to men, and this may also be explained by a higher vulnerability among women.…”
Section: Skorge Et Almentioning
confidence: 99%
“…4,5,17,24 Vrouwen -rooksters én niet-rooksters -melden vaker luchtwegsymptomen dan mannen, en consulteren vaker de huisarts voor luchtwegklachten. [25][26][27][28][29] Wij maten de kwaliteit van leven met een algemene vragenlijst (SF-36) en een ziektespecifieke vragenlijst (QOL-RIQ). De SF-36 is betrouwbaar, gevoelig en valide gebleken bij patiënten met Men mag daarom verwachten dat het onafhankelijke verband tussen dyspneuscore en kwaliteit van leven ook gevonden zal worden bij vrouwelijke rokers.…”
Section: Resultaatunclassified